OLSR Fuzzy Cost (OLSR-FC): uma extensão ao protocolo OLSR baseada em lógica Fuzzy e aplicada à prevenção de nós egoístas - José, Diógenes Antonio Marques (2014)
This work contributes with an extension to the Optimized Link State Routing protocol (OLSR) called Fuzzy Cost OLSR (OLSR-FC). In order to prevent selfish nodes as well as to improve the traffic flow over Mobile Ad-hoc Networks (MANETs), the routing metrics implemented in OLSR-FC make use of a Fuzzy Inference System (FIS) composed of 8 inference rules. Aiming at the choose of paths with low packet loss, better energy capacity and high connectivity, OLSR-FC implements a procedure of election of routes that takes into account the following parameters: Packet Loss Index (PLI), Residual Energy (RE) and Connectivity Index (CI). The OLSR-FC was evaluated by simulation through the NS- 2, in which two scenarios were implemented: a static one with 10 nodes (in testing phase), and a mobile one with up to 50 nodes. In the former scenario, a comparison was made between OLSR-FC and the original OLSR protocol which results showed that OLSR-FC overcomes OLSR in terms of throughput the packet loss. In the latter scenario, besides the original OLSR protocol, OLSR-FC was also faced up with the OLSR-ETX, OLSR-ML and OLSR-MD extensions in terms of the following performance metrics: throughput, energy consumption, packet loss rate, overhead, delay end-to-end, jitter, and packet delivery rate. In this context, results pointed that OLSR-FC achieved better performance in scenarios with a maximum of 10% of selfish nodes in comparison with every OSLR extension and the OLSR. Besides, by evaluating the main network performance metrics, such as throughput and delivery packet rate, OLSR-FC achieved eleven favorable cases against five cases in comparison with OLSR protocol.